Anti-Thymocyte Globulin Prophylaxis in Patients With Hematological Malignancies Undergoing Allogeneic Hematopoietic Stem Cell Transplantation: An Updated Meta-Analysis - Yang, Xue; Li, Dongjun; Xie, Yao (Frontiers in Oncology, 2021)
Background Anti-thymocyte globulin (ATG) prophylaxis reduces graft-versus-host disease (GVHD) incidence. This meta-analysis aimed to explore the long-term efficacy of ATG and the influencing factors in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods PubMed, Embase, and Cochrane databases were searched for the relevant studies published up to August 2020. Data from randomized controlled trials (RCTs) on ATG prophylaxis for GVHD prevention in allo-HSCT patients were extracted. Results A total of eight relevant RCTs (1,348 patients) were included. ATG significantly reduced the incidence of grade III–IV aGVHD (P = 0.001) and cGVHD (P < 0.001). ATG significantly improved the GVHD relapse-free survival (GRFS) (P < 0.001). The immunosuppressive regimen (number and dose of immunosuppressants) was significantly reduced when using ATG (P = 0.005). Epstein-Barr virus (EBV) reactivation was high in patients receiving ATG (P = 0.003). No significant differences were detected in relapses, overall survival (OS), relapse-free survival (RFS), and non-relapse mortality (NRM) between the ATG and no ATG groups. Subgroup analyses revealed that the donor type and ATG formulation might be the possible sources of heterogeneity among the included studies. Meta-regression analysis showed that the cumulative dose of ATG did not affect GVHD, OS, relapse, RFS, and NRM. Conclusion Although ATG had no significant effect on relapse, RFS, and NRM, it significantly reduced the occurrence and severity of GVHD, improved the GRFS, and reduced the number and dose of immunosuppressants in patients undergoing allo-HSCT.